Variations in alveolar partial pressure for carbon dioxide and oxygen have additive not synergistic acute effects on human pulmonary vasoconstriction. - Croft, Q; Formenti, F; Talbot, N; Lunn, D; Robbins, P; Dorrington, K (Public Library of Science, 2013)
The human pulmonary vasculature constricts in response to hypercapnia and hypoxia, with important consequences for homeostasis and adaptation. One function of these responses is to direct blood flow away from poorly-ventilated regions of the lung. In humans it is not known whether the stimuli of hypercapnia and hypoxia constrict the pulmonary blood vessels independently of each other or whether they act synergistically, such that the combination of hypercapnia and hypoxia is more effective than the sum of the responses to each stimulus on its own. We independently controlled the alveolar partial pressures of carbon dioxide (Paco 2) and oxygen (Pao 2) to examine their possible interaction on human pulmonary vasoconstriction. Nine volunteers each experienced sixteen possible combinations of four levels of Paco 2 (+6, +1, -4 and -9 mmHg, relative to baseline) with four levels of Pao 2 (175, 100, 75 and 50 mmHg). During each of these sixteen protocols Doppler echocardiography was used to evaluate cardiac output and systolic tricuspid pressure gradient, an index of pulmonary vasoconstriction. The degree of constriction varied linearly with both Paco 2 and the calculated haemoglobin oxygen desaturation (1-So2). Mixed effects modelling delivered coefficients defining the interdependence of cardiac output, systolic tricuspid pressure gradient, ventilation, Paco 2 and So2. No interaction was observed in the effects on pulmonary vasoconstriction of carbon dioxide and oxygen (p>0.64). Direct effects of the alveolar gases on systolic tricuspid pressure gradient greatly exceeded indirect effects arising from concurrent changes in cardiac output.